The Agencies: Key instruments for managing development and innovation (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2022)
Because they are efficient instruments for implementing territorial development policies, development and innovation agencies have attracted the attention of governments and multilateral organizations, which study, create and promote them, hence the diversity of research aimed at systematizing their characteristics and management models. There are more than 15,000 organizations of this type in the world, characterized by their diversity in terms of objectives, size and instruments; by their excellent human resources and, fundamentally, by their encouragement of territorial governance processes and promotion of innovation. This article is a partial synthesis of a broader research that is part of the interest in understanding the characteristics of development and innovation agencies and, particularly, in identifying the key dimensions or aspects addressed by studies to describe them as a basis for future research.
Keywords: development agencies; innovation agencies; innovation policies; territorial development